Transmission of family identity and consumer response: do consumers recognize family firms? - IBÁÑEZ CAAMAÑO, MARÍA JOSÉ; Manuel Alonso Dos Santos; Orlando Llanos-Contreras (My University, 2021)
PurposeCommunicating the identity of a family business generates positive results in consumer response. The paper aims to understanding how the efficient transmission of family identity can influence consumer behavior is essential for designing family firms' marketing communication strategies.Design/methodology/approachAn experimental study based on the eye-tracking technique was designed to determine how attention to (familiar vs non-familiar) visual stimuli on a website influences consumer recognition of a family firm status and how it influences consumer behavior. A sample of 212 individuals was exposed to (simulated) websites of family and non-family firms in the hospitality industry to capture information about their eye movements and measure visual attention to specific stimuli that communicated family identity.FindingsVisual attention has a direct and positive influence on recognizing family firm's identity (FFI). Through FFI, visual attention has an indirect positive effect on trust in the company and attitude toward the brand (BraAtt). Trust in a firm positively affects purchase intention (PurInt).Originality/valueIt is known that consumers can perceive a FFI; however, there is no study on the sensory mechanisms operating in consumers' perceptions of family identity. The study contributes to understanding how consumers can perceive a FFI. This study proposes a novel method for evaluating consumer responses by transmitting family business identity on digital platforms.
Keywords: consumer responses; eye-tracking; family firm branding; family firm identity; family firm reputation; identity transmission; visual attention